Disturbance Observer-Based Intelligent Control for Trajectory Tracking in Redundant Robotic Manipulators - Al-Mola, Mohammed H. A.; Abdelmaksoud, Sherif I. (International Journal of Robotics and Control Systems, 2025)
Redundant robotic manipulators require advanced control strategies to maintain stability and precision in the presence of dynamic disturbances. This study proposes an intelligent control scheme integrating Active Force Control (AFC) with a Proportional–Integral–Derivative (PID) controller to enhance the performance of a two-degree-of-freedom (2-DOF) robotic manipulator. The proposed AFC-PID controller is designed to suppress the effects of external disturbances, including torque noise. Comparative simulations demonstrate that the AFC-PID approach outperforms the conventional PID controller, providing improved stability and tracking accuracy in both manipulator links. Moreover, it compared with the Sliding Mode Control (SMC) control to verify the efficiency of the proposed controller. Quantitatively, the Integral Square Error (ISE) improvements compared to PID for link 1 and link 2 are 82.83% and 65.57%, respectively. Under disturbance conditions, performance gains are also observed, with ISE reductions of 86.2% and 65.36% for links 1 and 2. These results confirm the robustness and effectiveness of the proposed controller in maintaining consistent performance under challenging conditions. This is a significant improvement, reflecting the superiority over the conventional systems.